Bentuk-Bentuk Pelanggaran Kode Etik Advokat - Muhammad Fathony; Akbar Maulana; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
A violation is an act that violates the provisions of the law, and each violation carries a penalty that must be done to compensate for the violation. Every profession has a code of conduct which is to monitor the conduct of the profession so that it does not violate the law. There are different types of violation of the law of ethics; one of them is the abstraction of justice by the lawyer who creates a false report. The application of the code of ethics for lawyers and the legal profession is very important, because it can be a guide for legal professionals, including lawyers. This code of conduct has been established so that a lawyer knows what his rights and responsibilities are and what he can and cannot do. The code of ethics is kept in writing, because it has the function of a human control system that prevents interference from others. Keywords: Forms of Violations, Code of Ethics, Advocates.